2019
DOI: 10.1007/jhep01(2019)075
|View full text |Cite
|
Sign up to set email alerts
|

Lifting of D1-D5-P states

Abstract: We consider states of the D1-D5 CFT where only the left-moving sector is excited. As we deform away from the orbifold point, some of these states will remain BPS while others can 'lift'. We compute this lifting for a particular family of D1-D5-P states, at second order in the deformation off the orbifold point. We note that the maximally twisted sector of the CFT is special: the covering surface appearing in the correlator can only be genus one while for other sectors there is always a genus zero contribution.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 67 publications
(75 reference statements)
1
69
0
Order By: Relevance
“…AdS 3 × S 2 × M 5 , so in this work we will focus on those for which M 5 supports an SU(2)structure 6 . We do this in part to try and ensure that we realise small N = (4, 0) rather than some larger superconformal algebra which contains this.…”
mentioning
confidence: 99%
“…AdS 3 × S 2 × M 5 , so in this work we will focus on those for which M 5 supports an SU(2)structure 6 . We do this in part to try and ensure that we realise small N = (4, 0) rather than some larger superconformal algebra which contains this.…”
mentioning
confidence: 99%
“…Here M 0 nn gives the shift in weight of the marginal field Φ = σ ε under the perturbation Φ = σ 0 , and n denotes the numbers of non-zero entries in ε. Because of charge conservation there are only 17 distinct values out of the 216 indices -see the discussion above(5.19).6 Marginal twisted fields: T 8 /Z 26.1 Torus correlators of descendant fieldsHere we want to investigate the lifting of marginal fields of the form ∂X − 1 2∂ To compute their correlation functions, we proceed again by mapping to the double cover. This means that we need to compute correlation functions of bosonic descendants on the torus.Our starting point for this is the torus correlation function for bosonic operators of…”
mentioning
confidence: 99%
“…(ii) If the covering surface is a higher genus surface, then computing the correlator is much harder. In [20] it was shown that the covering surface is a sphere when the first D joins two copies of the CFT, and the second D undoes this join. But the covering space is a torus if the first D splits a multiwound copy of the CFT, and the second D rejoins the components.…”
Section: Deforming the Cftmentioning
confidence: 99%
“…(b) The above relation between δḠ andḠ (1) is relevant to an issue discussed in [20]. If we are computing the lift of the dimension to order λ 2 , then should we have to worry about the corrections to the state upto order λ 2 ?…”
Section: The Goal Of This Papermentioning
confidence: 99%
See 1 more Smart Citation